New developments in epidemiological research on dietary patterns associated with chronic kidney disease - Huang, Huixing; Yu, Cuiying; Sha, Pengjie; Chen, Leilei; Wang, Rongrong; Wei, Yanli (Frontiers in Nutrition, 2026)
Chronic kidney disease (CKD) represents a global health challenge, for which dietary modification serves as a profound preventive and interventional strategy. This article systematically examines and compares evidence from experimental and observational studies regarding the associations between the Mediterranean Diet (MD), Dietary Approaches to Stop Hypertension (DASH), New Nordic Renal Diet (NNRD), lacto-ovo-vegetarian diet (VD), and Chinese dietary patterns with CKD. Comprehensive analysis indicates that both MD and DASH exert significant preventive and protective effects against CKD. The NNRD demonstrates unique advantages in the precise management of phosphorus and protein intake among mid-to-late stage CKD patients. Meanwhile, VD, which is predominantly based on plant protein, contributes to the improvement of renal function parameters. However, in contrast, this review identifies a critical gap in the current evidence base: a severe scarcity of high-quality studies focusing on traditional Chinese dietary patterns. In conclusion, although international dietary patterns offer valuable insights, future research should prioritize the investigation of local dietary habits. Large-scale prospective studies are warranted to develop and validate dietary patterns tailored for CKD prevention and management within the Chinese population, thereby providing more targeted dietary recommendations.